Impact of Dairy Farming on Livelihood of Farmers - M. K. Rathod; V. P. Chandankar (Journal of Agricultural Extension Management, 2015)
The study was conducted in Wardha district of Vidarbha region of Maharashtra State with a sample size of 100 farmers from 10 villages. Data were collected on personal, socio-economic, situational and psychological profile of farmers, farming system and socio-economic status of farmers with rne help of a prestructured and pre-tested interview schedule. Regarding the impact of dairy farming, all the livelihood indicators of respondents significantly increased during the period of dairy farming. The percentage change increased by 87.49 per cent, 76.26 percent, 63.38 percent, 17.56 percent, 13.97 percent and 6.60 percent in case of physical capital, natural capital, financial capital, human capital, social capital and food security respectively. The overall impact of dairy farming on livelihood of farmers was highly significant and increased by 30.08 per cent